THE EFFECTIVE OF SMART PIANO TO ENHANCE PIANO SKILLS ON CHILDREN - Chang Liu; Md Jais Ismail, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to explore the potential benefits and effectiveness of incorporating smart pianos in the piano learning process for children. The research investigates the impact of smart piano teaching on enhancing piano skills among children. The participants of this study consist of students aged 4 to 6 years old, who are enrolled in a piano learning program that incorporates smart pianos. The research examines the students' progress over a designated period, comparing it with a control group using traditional piano instruction methods. The findings of this study contribute to the understanding of the benefits and limitations of smart piano education in piano education. The results reveal that smart pianos provide interactive learning experiences, including visual feedback, practice assistance features, progress tracking, and individualized learning options. These features positively impact students' engagement, motivation, and overall piano skill development. The implications of this research suggest that smart piano can be a valuable tool in piano education, enhancing students' learning experiences and promoting their overall musical growth. The study calls for further research with larger sample sizes and longer duration to validate and extend these initial findings.